Qualidade da atenção básica e sua relação com a vulnerabilidade social nos municípios do Nordeste do Brasil - Souza, Katyucia Oliveira Crispim de (2020)
Introduction: In the last ten years, the Brazilian Ministry of Health has prioritized the assessment of the quality and access to SUS health services, especially in Primary Care (PC). Nevertheless, there are several challenges for the qualification of this component of care due to the close relationship between social characteristics and health production. The research had two objectives: 1) To analyze the quality of primary care and its relationship with social vulnerability in the municipalities of the Brazilian Northeast; 2) To analyze the spatial distribution of the quality of primary care through the certifications obtained in the third cycle of PMAQ-AB in the municipality of Aracaju/SE. Methods: This is an ecological study with spatial analysis that used secondary data from the National Program for Access and Quality Improvement in Primary Care (PMAQ-AB, as per its Portuguese acronym). The dependent variable corresponded to the certifications of the PC teams in the Northeast and in Aracaju that took part in the third cycle of PMAQ-AB. In order to represent the social vulnerability of the northeastern municipalities, we selected the Municipal Social Vulnerability Index (IVS, as per its Portuguese acronym) as an independent variable; as for Aracaju, we used the Health Vulnerability Index proposed by Peixoto (2020). In the spatial analysis, we used univariate global (I) and local (LISA) Moran indexes. We used bivariate analyzes to examine the relationship between the quality of PC and IVS in the Northeast. The teams assessed by PMAQ-AB in Aracaju were analyzed according to their geographical location and the results of the certifications. Results: There is a spatial correlation between municipalities with high performance of PC whose neighbors also present high performance, except for Maranhão and Sergipe. The bivariate analysis highlighted the presence of high-low spatial groupings, mainly in municipalities in the states of Piauí, Ceará, Rio Grande do Norte, Pernambuco and Bahia, which corresponds to areas of low vulnerability with high quality of PC. Maranhão stood out because it presented low performance of PC in a large number of municipalities with high vulnerability. In Aracaju, there is a greater availability of teams in neighborhoods with high demographic density and high vulnerability. Moreover, there is a greater concentration of teams with regular and poor performance in neighborhoods with high vulnerability. Conclusion: The study has revealed the presence of a spatial relationship between indicators of social vulnerability and quality of PC, thereby suggesting that the quality of PC may be related to the social vulnerability of the enrolled population.